2014
DOI: 10.1016/j.hemonc.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

T2∗ MRI changes in the heart and liver of ex-thalassemic patients after hematopoietic stem cell transplantation

Abstract: The issue of iron overload is still remained as the main problem in ex-thalassemic patients after HSCT. We found T2(∗) MRI technique a quite beneficial method for following up the patients after transplantation. Obviously, planning large controlled trials associated with liver biopsy results after transplantation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…However, the hepatic T2* value was decreased, and hepatic iron deposition was aggravated. This finding is consistent with that reported by Amir Ali Hamideh et al, who showed cardiac and hepatic iron deposition changes after HSCT in thalassemia patients ( 32 ). After HSCT, thalassemia patients obtain effective erythropoiesis.…”
Section: Discussionsupporting
confidence: 93%
“…However, the hepatic T2* value was decreased, and hepatic iron deposition was aggravated. This finding is consistent with that reported by Amir Ali Hamideh et al, who showed cardiac and hepatic iron deposition changes after HSCT in thalassemia patients ( 32 ). After HSCT, thalassemia patients obtain effective erythropoiesis.…”
Section: Discussionsupporting
confidence: 93%
“…Hepatic and myocardial T2* values before and 6 months after HCT were measured and analyzed. Results showed that there was not a statistically significant increase in myocardial T2* values after HCT, instead Hepatic T2* values significantly decreased after HCT showing an increase of the liver iron 35…”
Section: Free Iron Toxicity During the Early Transplant Phase (Beforementioning
confidence: 77%
“…Iron overload post HSCT has been associated with mainly long term complications including endocrinopathies, cardiac and liver dysfunction [43, 79,80]. The timing and method of iron overload assessment however is not defined in pediatrics post HSCT and centers develop their own strategies to detect and then treat.…”
Section: What Is the Optimal Treatment Approach For Transfusional Hemmentioning
confidence: 99%